Laser Process for Selective Emitter Silicon Solar Cells. (5th March 2012) - Poulain, G.; Blanc, D.; Focsa, A.; Bazer-Bachi, B.; Gauthier, M.; Semmache, B.; Pellegrin, Y.; Le Quang, N.; Lemiti, M.
Abstract : Selective emitter solar cells can provide a significant increase in conversion efficiency. However current approaches need many technological steps and alignment procedures. This paper reports on a preliminary attempt to reduce the number of processing steps and therefore the cost of selective emitter cells. In the developed procedure, a phosphorous glass covered with silicon nitride acts as the doping source. A laser is used to open locally the antireflection coating and at the same time achieve local phosphorus diffusion. In this process the standard chemical etching of the phosphorous glass is avoided. Sheet resistance variation from 100 Ω/sq to 40 Ω/sq is demonstrated with a nanosecond UV laser. Numerical simulation of the laser-matter interaction is discussed to understand the dopant diffusion efficiency. Preliminary solar cells results show a 0.5% improvement compared with a homogeneous emitter structure.